The new voice of America: Countering Foreign Propaganda and Disinformation Act. Issue 2 (3rd July 2017) - Hall, Holly Kathleen
Abstract: Just before the 2016 Christmas holiday weekend, President Barack Obama quietly signed the 2017 National Defense Authorization Act (NDAA) into law. Deep within the act is a controversial provision called the Countering Foreign Propaganda and Disinformation Act (CFPDA), which establishes a Global Engagement Center under the State Department and consolidates the power of several federal broadcasting entities under one authority. This center will coordinate efforts to counter foreign propaganda, mainly from Russia and China, that is aimed at undermining the United States' national security interests. The consolidation of power creates some concerns regarding journalistic independence and credibility for media outlets such as the Voice of America. The new Trump administration's perceived amicable relationship with Russia also generates uncertainty around the commitment to fight Russian disinformation and propaganda. This essay argues that the US does in fact need some kind of governmental entity devoted to the creation of counter-propaganda, and then concludes there are deficiencies and vulnerabilities with the CFPDA, especially a lack of adequate administrative oversight. Based on this conclusion, as well as on lessons gleaned from how other nations have dealt with Russian disinformation campaigns, the essay offers tentative recommendations as to what an effective governing structure would look like.